Endovascular management of anterior falcotentorial dural arteriovenous fistulas: importance of functionality of deep venous system and existence of accompanying choroidal arteriovenous malformation. (28th July 2021) - Islak, Civan; Bagcilar, Omer; Nacar Dogan, Sebahat; Korkmazer, Bora; Arslan, Serdar; Kizilkilic, Osman; Kocer, Naci
Abstract : Background: Anterior falcotentorial junction dural arteriovenous fistulas (AFDAVFs) are the most deeply located and most complex type of tentorial fistula due to their location and vascular anatomy. We aimed to make new angiographic definitions of AFDAVF nidus and functionality of the deep venous system of the brain and thereby provide a safer approach for endovascular treatment. Methods: We retrospectively examined 18 patients with AFDAVF who received endovascular treatment at our neuroradiology department between June 2002 and May 2019. Pre- and post-treatment clinical assessments were performed using the modified Rankin Scale. AFDAVF niduses were defined as mixed-type or pure-dural-type on the basis of whether choroidal arteriovenous malformation was coexisting or not, respectively. The deep venous system was denoted as functional or nonfunctional. Results: We included 13 men and 5 women (mean (range) age, 47.2 (31–62) years). We evaluated 15 patients with pure-dural-type AFDAVFs and three with mixed-type AFDAVFs. Complete occlusion of the fistula was achieved in 15/18 patients. Three patients had transient neurologic symptoms. In two patients these were due to mild thalamic ischemia and in the third patient was due to tectal venous ischemia, all in mixed-type AFDAVF. One patient also developed Parinaud syndrome due to compression of the tectal plate by a thrombosed large vein of Galen. No patients died or developed permanent morbidity. Conclusion: Evaluating AFDAVFs as described here using our new subtyping model will help improve analysis of the malformation and development of a safer endovascular strategy, and hence may prevent periprocedural complications and improve treatment safety.